Characterization of Molecularly Imprinted Polymers (MIPs) as Cholesterol-Absorbing Materials - Nadia, Nadia; Kurniawati, Desy; Alizar, Alizar (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Molecularly Imprinted Polymer (MIP) membranes as cholesterol absorbers have been successfully synthesized. MIP membranes can absorb cholesterol molecules because they have cavite (pores) and active groups that are selective and sensitive to cholesterol molecules. MIP membranes are synthesized from butyl acrylate monomers, cross-linkers, ethylene glycol dimethacrilate (EGDMA), initiators of 2- 2-dimethoxy-2-phenylacetophenone (DMPP, sodium dodecyl sulfate (SDS) as surfactants, and cholesterol as templates. MIP membranes are synthesized using photopolymerization irradiated with UV light. The results obtained in the form of powder solids can be characterized using UV-Vis spectrophotometry. The results obtained by UV-Vis spectrophotometry showed that the MIP membrane prepared a standard curve with a linear regression equation y = 0.0054x-0.007 with a value of R2 = 0.9982. This suggests that MIP membranes are selective and sensitive to analytes. At optimum absorption of the MIP-cholesterol membrane can absorb cholesterol molecules in the amount of 0.020 grams of cholesterol composition within 20 minutes